A Multi-Criteria Portfolio Analysis of Hedge Fund Strategies - David E. Allen; Michael McAleer; Abhay K. Singh (Tinbergen Institute, 2017)
This paper features a tri-criteria analysis of Eurekahedge fund data strategy index data. We use nine Eurekahedge equally weighted main strategy indices for the portfolio analysis. The tri-criteria analysis features three objectives: return, risk and dispersion of risk objectives in a Multi-Criteria Optimisation (MCO) portfolio analysis. We vary the MCO return and risk targets and contrast the results with four more standard portfolio optimisation criteria, namely the tangency portfolio(MSR), the most diversified portfolio (MDP), the global minimum variance portfolio (GMW), and portfolios based on minimising expected shortfall (ERC). Backtests of the chosen portfolios for this hedge fund data set indicate that the use of MCO is accompanied by uncertainty about the a priori choice of optimal parameter settings for the decision criteria. The empirical results do not appear to outperform more standard bi-criteria portfolio analyses in the backtests undertaken on our hedge fund index data.
Keywords: G15; G17; G32; C58; D53; 330; MCO; Portfolio Analysis; Hedge Fund Strategies; Multi-Criteria Optimisation